INVITED REVIEW‐OFF‐SITE PET IMAGING PROGRAMS: CHALLENGES AND OPPORTUNITIES. Issue 1 (18th September 2013) - LeBlanc, Amy K.; Morandi, Federica
<x xml:space="preserve">Abstract</x> Veterinarians are gaining interest in and access to Position Emission Tomography (PET and PET/CT) imaging for both clinical and research applications. This manuscript provides an overview of how veterinarians may approach the use of off‐site PET and PET/CT scanners already in use for human medical imaging in order to gain access to this technology without direct investment in costly equipment and infrastructure. An overview of general procedures, animal transport, and radiation safety considerations is offered along with references to key regulatory statutes that may apply to the operation of PET imaging facilities in individual states.